Sistem Informasi Pemasaran Sebagai Sistem Informasi Sumber Daya Informasi - Warno, Warno (potensio, 2008)
Complexity and tight business require a business to developInformation Organization System to give an excellence competitionin business. The important point in Marketting Information Systemthat is: Accounting Information System, Marketing Risset andMarketting Inteligence procesed with database to produce: product,promotion, place and price oriented in customer satisfaction. IRIS issystem that provided an information about information companyresources for the user in a company.Key Words : 4P (product, promotion, place, price); IRIS